MEDROBO: Automated Medicine Delivery and Patient Monitoring System - G, Kalpana; R, Sai Poojitha; Varun, Mukka; P, Sriharsha (Journal of Electronics and Informatics, 2024)
The research aims to develop an innovative solution to automate the delivery of medicine to patients and monitor their vital parameters in healthcare facilities. Traditional methods often rely on human interventions for medicine delivery and patient monitoring, leading to inefficiencies and potential errors. To address these challenges, the proposed study introduces a robotic system capable of line-following method and real-time health parameter monitoring. The core functionality of the system revolves around a robot equipped with various sensors. The robot navigates hospital corridors by following predefined lines, allowing it to reach patients’ rooms without human assistance. RFID tags attached to patient beds facilitate the robot in identifying and locating specific patients, ensuring accurate medicine delivery. Furthermore, the robot integrates vital sign monitoring capabilities, including heart rate, Spo2, blood pressure, and temperature.